An Ecclesially Located Exegesis Informed by Augustine's "De Doctrina Christiana" - Strahan, Joshua Marshall (Journal of theological interpretation, 2012)
This article opens with an example of what a Christian interpretive paradigm might look like. For help with this, it turns to Augustine's De Doctrina Christiana (DDC), which will be shown to have a hermeneutic with a priori theological convictions. Augustine's ecclesially located exegetical framework results in a hermeneutic that (1) calls for humble, submissive, and virtuous readers; (2) highly values authorial communicative intent; (3) is nonetheless open to polysemy; and (4) delimits interpretations by appealing to the rule of faith, the double love commandment, and clearer canonical texts. Insights from DDC are then brought into conversation with the hermeneutical paradigms of Räisänen and Stendahl. In brief, Augustine's hermeneutic clashes with Räisänen's, because Augustine reads Scripture from the standpoint of Christian faith, whereas Räisänen attempts to read from a so-called neutral standpoint. Regarding Stendahl's exclusive privileging of authorial intent, an ecclesially located theology would seem to challenge Stendahl because of (1) how NT writers often seem to read OT texts beyond the intent of the OT author, and (2) the inability of sola scriptura to determine crucial theological doctrines. The last section of this article notes how Augustine's approach to delimiting polysemic interpretations holds together many of the strengths offered by contemporary theological interpreters, including Max Turner, Richard Hays, Joel Green, Stephen Fowl, A. K. M. Adam, Richard Briggs, and others. The hope is that, by bringing DDC into the conversation, this article can contribute to the elusive task of making room for, while simultaneously bounding, polysemy in biblical interpretation.